Metaphysical balm and the poet as legislator - Betty, Michèle Anne (School of Languages and Literatures, 2016)
This essay was born of a desire to understand the relationship between poetry and politics in a meaningful and current way. The twentieth century has seen atrocities that have taken place on an unprecedented scale: times of historical and social extremity, states of exile, censorship, military occupation, political persecution, torture, warfare, assassination, apartheid and, more recently, forms of violent terrorism. This essay will consider the function of poetry in a world overcome and consumed by violence. The essay will begin with a consideration of the political function of the ideas expressed in Percy Bysshe Shelley's A Defence of Poetry (hereinafter A Defence). Shelley's notion of the promise of art and what it de facto delivers, and his ideas on the significance of poems in the context of politics will be examined. The essay will then consider the views of the Russian Formalists on how to establish the "literariness" of a text and the ability of a text to "defamiliarise", as well as the devices that can be used by a poet to achieve literariness and defamiliarisation. It will touch on the work of Mikhail Bakhtin and his concepts of folk humour and grotesque realism in a text. Carolyn Forché's idea of poetry as a witness of a lived experience, as enunciated in her text Against Forgetting: Twentieth-Century Poetry of Witness, will be discussed. Thereafter, the essay will consider Viljoen and Van der Merwe's notions of liminality in literature, as expounded in their text Beyond the Threshold, and their explanation of how language can act as a transformative vehicle. In order to illustrate these concepts practically, the essay will analyse two South African poetry collections, namely: Nathan Trantraal's Chokers en Survivors and Oswald Mtshali's Sounds of a Cowhide Drum. The analyses will reveal what distinguishes mere resistance poetry and political diatribe from poetry that is lasting and effective.